Penile rehabilitation effectiveness after prostate cancer treatment: A systematic review of randomized controlled trials - Prasad, Roshan; Wanjari, Mayur; Lamture, Yeshwant R.; Late, Sampada; Sharma, Ranjana (Narra Sains Indonesia, 2023)
Prostate cancer treatment can significantly impact erectile function, and penile rehabilitation has been proposed to improve the impacts. However, the effectiveness of penile rehabilitations after treatment of prostate cancer is scarce. The aim of this systematic review was to evaluate the effectiveness of different interventions of penile rehabilitation program after prostate cancer treatment. We conducted a comprehensive search of electronic databases, PubMed and Google Scholar, to identify randomized controlled trials that evaluated interventions for penile rehabilitation after prostate cancer treatment. Studies that met our inclusion criteria were systematically reviewed, and data were synthesized and analyzed. We identified 11 randomized controlled trials that evaluated different interventions for penile rehabilitation after prostate cancer treatment. The interventions included the use of phosphodiesterase type 5 inhibitors, intracavernous injections, vacuum erection devices, and penile rehabilitation programs. The data suggest that these phosphodiesterase inhibitors, intracavernous injections, vacuum erection devices, and penile rehabilitation programs are promising in improving erectile function after prostate cancer treatment. However, the optimal timing and duration of these interventions remain unclear, and there is a need for further research to determine their long-term effectiveness and safety. Healthcare providers should consider individualized approaches to penile rehabilitation, taking into account patient characteristics and preferences.